Ganoderma tsugae suppresses the proliferation of endometrial carcinoma cells via Akt signaling pathway - Tsai, Yi‐Ting; Kuo, Pin‐Hung; Kuo, Han‐Peng; Hsu, Chih‐Yu; Lee, Yi‐Jen; Kuo, Chao‐Lin; Liu, Jah‐Yao; Lee, Shou‐Lun; Kao, Ming‐Ching (Environmental toxicology, 2021)
Ganoderma is one of the common medicinal mushrooms in traditional Chinese medicine. Previous researches have unveiled the multifaceted biological activity of Ganoderma extract. Ganoderma tsugae has been investigated the potential on curing prostate, colon, lung, epidermoid, breast and ovarian cancers, but not including endometrial cancer. Endometrial cancer is a gynecological malignant tumor with serious drug resistance problem in clinical cancer treatment. This study aimed to demonstrate the first study of Ganoderma on treating endometrial cancer. The Ganoderma tsugae ethanol extract (GTEE) could suppress the proliferation of endometrial cancer cells HEC‐1‐A, KLE, and AN3 CA. GTEE also induced G1/S phase arrest and mitochondria‐mediated apoptosis in endometrial cancer cells. Furthermore, the Akt signaling pathway could be suppressed by GTEE. Therefore, our results suggest for the first time that GTEE has the potential to be an adjuvant therapeutic agent in the treatment of endometrial cancer.